Wage Variability in the 1970s: Sectoral Shifts or Cyclical Sensitivity? - Shaw, Kathryn L. (The Review of Economics and Statistics, 1989)
The recent debate questioning whether unemployment in the 1970s represents sectoral adjustment or cyclical variation is expanded to examine comparable causes of real wage variability. Using Panel Study of Income Dynamics panel data, real wages respond more to persistent sectoral shocks than cyclical shocks in the 1970s, making recent estimates of procyclical wage variability appear weak in perspective. Employing a model of endogenous sector-specific individual skills, older workers earning economic rents are shown to have the greatest wage response to sectoral shocks. These results are consistent with the hypothesis that short run cyclical shocks may be met with hours adjustment, as specified in implicit or explicit contracts, but that persistent shocks require wage adjustment. Copyright 1989 by MIT Press.